Escherichia coli 0157:H7 general characterístics and occurence in Brazil - Paula, Cheila Minéia Daniel de; Loiko, Márcia Regina; Tondo, Eduardo Cesar (Clinical and Biomedical Research, 2014)
Escherichia coli O157: H7 is the major foodborne pathogens in the present, since it has been responsible for severe outbreaks food in many countries. Several studies evaluate numerous food samples indicating a low frequency of isolation of E. coli O157:H7 in Brazilian products. However, these data should be interpreted carefully since in Brazil there is no systematic monitoring that might indicate the true situation of the occurrence of this bacteria in food and several clinical cases of Hemolytic Uremic Syndrome (HUS), have been recorded, including one associated with E. coli O157:H7. Moreover, numerous researches has been indicating the increasingly frequent isolation of microorganisms in animal reservoirs, mainly in cattle, suggesting the necessity of monitoring of shiga toxin-producing strains (STEC), because in a globalized world, emerging microorganisms could be rapidly disseminated. The objective of this study is to present the current situation of E. coli O157: H7 in Brazil.